Optical Properties and Aging Characteristics of Blackchrme Surface on Different Textures of Aluminium Substrates - Kanchana Trakulcoo; Saowanee Niemsorn; Patcharee Pitaksenpanich (ASEAN Journal on Science and Technology for Development, 1987)
Optical Properties and Aging Characteristics of Blackchrme Surface on Different Textures of Aluminium Substrates